Cytogenetic evidence of hybridization in Prosopis alba, P. hassleri, and P. fiebrigii in the semiarid-humid Chaco transition - Vega, Carmen Delcira; Cosacov, Andrea; Acosta, María Cristina (Taylor and Francis, 2023)
Hybridization is a common and widespread phenomenon in vascular plants, leading to genetic exchange between related species. Interspecific hybridization has been extensively reported in Prosopis, a key genus of the Gran Chaco Americano, when species grow in sympatry or have adjacent distributions. Here, we performed a cytogenetic study in a hybrid zone of Prosopis alba, P. hassleri, and P. fiebrigii in southern South America. We characterized the karyotypes of pure species and the putative interspecific hybrids using chromosome fluorescent banding. Two karyotypes according to the heterochromatin pattern were identified, one corresponding to P. alba and the other to P. hassleri and P. fiebrigii; hybrid individuals presented P. alba or P. hassleri/P. fiebrigii karyotypes. The karyotypic formula and the number of nucleolar organizer regions were the same for all the studied morphotypes. Chromosome similarity among different species of the genus allows a continued hybridization and introgression between species and lends support to the hypothesis of a relatively recent diversification of Prosopis. Studying karyotype variation within a population could be a novel approach to the cytogenetic study of hybrids in the future.